Goosebumps presents be careful what you wish for - Gerver, Jane E.; Lazer, Charles; Stine, R. L. (New York : Scholastic, 1997)
Samantha, the laughingstock of the girls' basketball team, meets someone who can grant her three wishes. But she isn't careful what she wishes for and they come true, turning her life into a living nightmare.
"A Parachute Press book"--T.p. verso.
2.5.
2.5
5-8
Keywords: Horror stories; Wishes -- Fiction; Horror fiction; Wishes -- Fiction